2021
DOI: 10.1080/13880209.2021.2010774
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Yougui pill combined with Buzhong Yiqi decoction in alleviating the sexual dysfunction in female rats through modulation of the gut microbiota

Abstract: Context Yougui pill combined with Buzhong Yiqi decoction (YPBYD) is used to relieve sexual dysfunction in clinical practice. Objective To investigate changes in microbial composition caused by sexual dysfunction and identify dominant bacteria related to YPBYD treatment. Materials and methods Female Sprague-Dawley rats were randomly divided into four groups ( n = 6): one group underwent Sham operation (Sham group), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Therefore, the discovery of novel therapeutic targets and the development of novel drugs for efficient and safe therapy of osteoporotic fractures are urgently warranted [ 34 ]. BZYQD is a widely used Chinese herbal formula for treating complicated diseases, including female stress urinary incontinence [ 35 ], sexual dysfunction [ 36 ], and OPF. However, the ingredients and therapeutic mechanisms of OPF require clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the discovery of novel therapeutic targets and the development of novel drugs for efficient and safe therapy of osteoporotic fractures are urgently warranted [ 34 ]. BZYQD is a widely used Chinese herbal formula for treating complicated diseases, including female stress urinary incontinence [ 35 ], sexual dysfunction [ 36 ], and OPF. However, the ingredients and therapeutic mechanisms of OPF require clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Modern studies have found that there is a new cholinesterase inhibitor in MBZYQD (Liu et al, 2010;Cui et al, 2015). MBZYQD may affect the key factors in the anti-inflammatory process by regulating intestinal microbiota (Wang et al, 2022) and may play a role in the occurrence and development of MG Zong et al, 2021). However, it is unclear whether MBZYQD can improve myasthenia gravis by regulating intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Yougui pill is a 10-component TCM remedy ( Table 1 ) and is well known in TCM for its therapeutic effects on impotence. With the development of research, it also was used to effectively treat sexual dysfunction ( Wang Y. et al, 2022 ). A randomized clinical trial involving 42 patients of DED found that 6 weeks of treatment with Yougui pill could significantly increase the IIEF-5 score of the patients compared with those of the placebo-treated group ( Zhia et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%